2020
DOI: 10.1002/glia.23839
|View full text |Cite
|
Sign up to set email alerts
|

Neuroglial transmitophagy and Parkinson's disease

Abstract: Mitophagy is essential for the health of dopaminergic neurons because mitochondrial damage is a keystone of Parkinson's disease. The aim of the present work was to study the degradation of mitochondria in the degenerating dopaminergic synapse. Adult Sprague–Dawley rats and YFP‐Mito‐DAn mice with fluorescent mitochondria in dopaminergic neurons were injected in the lateral ventricles with 6‐hydroxydopamine, a toxic that inhibits the mitochondrial chain of dopaminergic neurons and blockades the axonal transport.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 95 publications
1
53
0
Order By: Relevance
“…In this study, electron microscopy and confocal microscopy determined that retinal ganglion cells transferred mitochondriacontained vesicles to retinal astrocytes to eliminate damaged mitochondria through so called transmitophagy. In the context of PD, the mechanism of transmitophagy may be crucial to maintain mitochondrial function in dopaminergic neurons and prevent neuroinflammation mediated by disrupted mitochondrial secretion (Morales et al, 2020). In this study, Morales and colleagues observed that damaged dopaminergic neurons via 6-OHDA infusion generated spheroid-like structure containing mitochondria and transferred them to adjacent astrocytes for digesting damaged mitochondria through STX17/Lamp1/Lamp2/LC3+ autophagolysosomes FIGURE 1 | Intercellular mitochondrial transfer.…”
Section: Extracellular Mitochondria As a Biomarker For Mitochondrial mentioning
confidence: 85%
See 1 more Smart Citation
“…In this study, electron microscopy and confocal microscopy determined that retinal ganglion cells transferred mitochondriacontained vesicles to retinal astrocytes to eliminate damaged mitochondria through so called transmitophagy. In the context of PD, the mechanism of transmitophagy may be crucial to maintain mitochondrial function in dopaminergic neurons and prevent neuroinflammation mediated by disrupted mitochondrial secretion (Morales et al, 2020). In this study, Morales and colleagues observed that damaged dopaminergic neurons via 6-OHDA infusion generated spheroid-like structure containing mitochondria and transferred them to adjacent astrocytes for digesting damaged mitochondria through STX17/Lamp1/Lamp2/LC3+ autophagolysosomes FIGURE 1 | Intercellular mitochondrial transfer.…”
Section: Extracellular Mitochondria As a Biomarker For Mitochondrial mentioning
confidence: 85%
“…Extracellular mitochondria and mtDNA may provide a glimpse into the status of tissue metabolism, disease severity and recovery in the CNS. (Morales et al, 2020). Collectively, the transmitophagy may be a mechanism of mitochondrial quality control through intercellular mitochondrial transfer in the CNS.…”
Section: Extracellular Mitochondria As a Biomarker For Mitochondrial mentioning
confidence: 99%
“…As mentioned above, astrocytes engulf the aggregated α-synuclein and damaged mitochondria released from neuronal cells and degrade neuronal waste via the proteasome and autophagy (mitophagy) pathways [94,95,234]. Thus, phagocytic activity of astrocytes is important for neuroprotection ( Figure 2).…”
Section: Upregulation Of Neuroprotective Properties In Astrocytesmentioning
confidence: 99%
“…The uptake of extracellular α-synuclein occurs via endocytosis in neurons and glial cells [91]. In particular, microglia and astrocytes are able to clean extracellular α-synuclein aggregates via internalization and degradation [92][93][94]. Recently, astrocytes were reported to engulf and degrade α-synuclein aggregates via proteasome and autophagy pathways [95], suggesting that astrocytes exert dopaminergic neuroprotection by clearing excess extracellular toxic α-synuclein.…”
Section: Disposal Of Neuronal Waste Productsmentioning
confidence: 99%
See 1 more Smart Citation